Healthcare Big Data Analytics : Computational Optimization and Cohesive Approaches - Abdulraheem, Muyideen; Abidemi Adeniyi, Emmanuel; Agravanshi, Subandhu; Albuquerque, Victor, Hugo C. de; Bamidele Awotunde, Joseph; Dauda Oladipo, Idowu; Ganeshkumar, M.; Gohil, Jay; Gopalakrishnan, E. A.; H. Jhaveri, Rutvij; Holi, Ganga; Kumar Bhoi, Akash; et al. (Intelligent Biomedical Data Analysis ,, 2024)
This book highlights how optimized big data applications can be used for patient monitoring and clinical diagnosis. In fact, IoT-based applications are data-driven and mostly employ modern optimization techniques. The book also explores challenges, opportunities, and future research directions, discussing the stages of data collection and pre-processing, as well as the associated challenges and issues in data handling and setup.